SYSTEMATIC REVIEW: PERSPECTIVE OF THE PHYTOCHEMICAL PROFILE AND BIOLOGICAL TESTS OF SOLALUM CAPSICOIDES (SOLANACEAE) FRUITS USING THE METHODI ORDINATIO PROTOCOL - da Silva, Thais Bordenowsky; Miguel, Obdulio Gomes; Miguel, Marilis Dallarmi; de Fátima G. Dias, Josiane; Montrucchio, Deise Prehs; Sartor, Elisiane de Bona; dos Anjos, Cintia Aparecida (Editora Impacto Científico, 2025)
Nightshades demonstrate therapeutic potential that warrants further investigation. Several members of the Solanaceae family are used to treat a range of clinical conditions, such as respiratory and ophthalmological diseases, Parkinson's disease, spasmodic conditions, and as anti-inflammatories. The objective of this study is to present a systematic review protocol for extracts of the species Solanum capsicoides (SOLANACEAE): prospecting the phytochemical profile and biological assays of the fruits. The literature search was conducted in the Web of Science (WoS), Science Direct, and Scopus databases, according to the protocols established by the Methodi Ordinatio (MO). Concurrently, based on the results, bibliometric network visualizations and mapping of specific results were performed using the VOSviewer® software. The results obtained from the presented texts may contribute information about the characteristics of this species, based on its chemical composition and biological activities, which were previously unknown to the scientific community.DOI: 10.56238/edimpacto2025.060-007